Utilización de los SIG para la generación de mapa de amenaza por deslizamientos, análisis de estabilidad del talud crítico y alternativas para mitigar la amenaza, caso de estudio tramo vial Dosquebradas- Santa Rosa (2020)
The product deals with the application of geographic information systems, and the management of quantitatively and qualitatively classified public information on the factors that intervene in mass movements, for the generation of landslide hazard maps